1996
DOI: 10.4141/cjas96-051
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant bovine somatotropin increases nutrient absorption by the proximal small intestine in sheep

Abstract: Dorset crossbred ewes were used to determine the effect of recombinant methionyl bovine somatotropin (bST) on small intestinal nutrient absorption. Ewes were kept indoors in individual pens and allowed free access to a concentrate diet (18% CP). (150 μg kg−1) or saline were subcutaneously injected once daily for 10 d. An in vitro assay system was used to estimate the rate of accumulation of 3H-3-O-methylglucose and 14C-proline by small intestinal segments. Feed intake and liveweight gain were similar in ewes a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1998
1998
2007
2007

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Similarly bST transgenic mice have intestinal weights and lengths that are greater than wild-type littermates , although glucose transport per milligram of intestinal tissue decreases by as much as 24% (Bird et al 1994c). Recently Bird et al (1996b) reported that duodenal glucose active transport and total proline transport were increased 25-30% in ewes administered recombinant bovine somatotropin for 14 d. No changes were detected in the rate of jejunal or ileal active glucose uptake. Bird et al (1996b) postulated that the site-specific nature of bST on glucose transport in sheep may be indirect via effects on enteroendocrine cells in the proximal gut.…”
Section: Other Peptides and Hormonesmentioning
confidence: 98%
See 1 more Smart Citation
“…Similarly bST transgenic mice have intestinal weights and lengths that are greater than wild-type littermates , although glucose transport per milligram of intestinal tissue decreases by as much as 24% (Bird et al 1994c). Recently Bird et al (1996b) reported that duodenal glucose active transport and total proline transport were increased 25-30% in ewes administered recombinant bovine somatotropin for 14 d. No changes were detected in the rate of jejunal or ileal active glucose uptake. Bird et al (1996b) postulated that the site-specific nature of bST on glucose transport in sheep may be indirect via effects on enteroendocrine cells in the proximal gut.…”
Section: Other Peptides and Hormonesmentioning
confidence: 98%
“…Recently Bird et al (1996b) reported that duodenal glucose active transport and total proline transport were increased 25-30% in ewes administered recombinant bovine somatotropin for 14 d. No changes were detected in the rate of jejunal or ileal active glucose uptake. Bird et al (1996b) postulated that the site-specific nature of bST on glucose transport in sheep may be indirect via effects on enteroendocrine cells in the proximal gut. Other studies regarding the role of somatotropin on intestinal absorption have been less clear.…”
Section: Other Peptides and Hormonesmentioning
confidence: 98%
“…Similarly, ovine growth hormone (oGH) and recombinant bovine somatotropin did not alter average daily live weight gain and feed intake (Muir et al 1983;Bird et al 1996). However, McLaughlin et al (1993) found that growth rate was increased and food conversion was improved by somatotropin.…”
Section: Discussionmentioning
confidence: 95%